Study on sediment size and discharge at Lebir River due to 2014 flood - Raja Irni Fatini, Raja Idnan (2016)
A study on sediment was conducted at the Lebir River. Sediment is solid material that deposited in a new location by a river. It can be in many shapes and size. The deposition of sediment process was effected depends on river flow. This study was conducted to determine type and size of sediment and sediment discharge at Lebir River. There are five station of sediment sample that was taken to get that parameter. The sediment grain size was analysing through Sieve Analysis as to get type of sediment and mean grain size while the concentration of sediment will be measured through Total Suspended Solid (TSS). Most of the sample has course sand, very course sand and fine gravel type based on Udden-Wentworth scale. There are different values for TSS starting from Station 1 until Station 5 with 520mg/l, 917mg/l, 1331mg/l, 1337mg/l and 422mg/l. By using three sediment transport function which are Engulend Hansen, Yang’s Stream and Colby Formula, the value of sediment discharge for each formula are quite different because the rate is related to the size of sediment. So that, Engulend Hansen Formula was preferred because meets the requirements compare to other function. The sediment discharge value by using this method starting from Station 1 until Station 5 are 0.159kg/m-s, 0.188kg/m-s, 0.087kg/m-s, 0.044kg/m-s and 0.006kg/m-s.